PELAKSANAAN GROSSE AKTA SEBAGAI PENGAKUAN HUTANG DALAM PERJANJIAN KREDIT PADA BANK PEMBANGUNAN DAERAH (BPD) CABANG MUARA BADAK KUTAI KARTANEGARA - Andi Mirdat Effendi (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTIn the application or implementation is not easy to determine whether the proposed deed grosse have met the formal requirements and materially . Particularly with respect to the material terms of the deed grosse . In practice poses many problems due to the development in the presence msayarakat grosse based on the deed of the bank credit agreement as an agreement in principal . Grosse deed of acknowledgment of debt that is overlaid with other agreements in the form of power or authority to sell and install security rights and others in the grosse deed is not allowed because it causes rancaunya in execution , ie whether the executions carried out against grosse deed of acknowledgment of debt or the mortgage certificate . So this violates the rule of law set forth in Article 224 HIR and fatwa No. MA . 213/229/85/UM-TU/Pdt April 16, 1985 so grosse aktapengakuan acknowledgment of debt was not pure debt debtor to a creditor within a certain amount and cause grosse deed of acknowledgment of debt is null and void and the implementation of the execution can not be carried out . And the payment in installments , interest and penalties and other costs to the costs of the execution are overlaid in a deed of acknowledgment of debt grosse can not be justified in accordance with the nature of the deed grosse to be purely unilateral declaration of debituryang admit a certain amount of money owed to creditors that after with the rules in Article 224 HIR and fatwa No. MA . 213/229/85/UM-TU/Pdt April 16, 1985 , while pencamtuman clause on payment in installments , interest and penalties and other costs to the cost of execution should be included in the deed of loan agreement only.